Cable product capable of inhibiting blooming and manufacturing method
By combining modified ammonium polyphosphate composite flame retardant and barrier fiber membrane-adsorbent composite, the aging and frost spraying problems of traditional cables in high temperature and high humidity environments are solved, and the excellent flame retardant performance and anti-frost function of the cable are achieved, extending the service life.
Patent Information
- Application Number
- CN202411687674.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-25
AI Technical Summary
Traditional cables are prone to aging and cracking in high temperature and high humidity environments, resulting in a decline in mechanical and electrical performance, increasing safety hazards, and are prone to frost spraying during long-term use, affecting the appearance and performance of the cable.
Using modified ammonium polyphosphate composite flame retardant and barrier fiber membrane-adsorbent composite material, cable products with excellent flame retardant properties and anti-blasting function were prepared through aluminum hydroxide coating and electrospinning technology.
It improves the flame retardant performance and mechanical strength of the cable, prevents the occurrence of frost spraying, extends the service life of the cable, and maintains good performance in high temperature and high humidity environments.
Smart Images

Figure BDA0005150038400000171
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cable manufacturing, and in particular relates to a cable product capable of inhibiting frost spraying and a manufacturing method thereof. Background Art
[0002] With the rapid development of modern industry and technology, cables, as an important carrier of power transmission and information transfer, are receiving more and more attention for their performance and safety.
[0003] Traditional cables mostly use materials such as polyvinyl chloride (PVC) as insulation layers. Although these materials have a certain flame retardant effect, they are prone to aging and cracking in harsh environments such as high temperature and high humidity. These problems will not only lead to the degradation of the mechanical and electrical properties of the cables, but may also cause safety accidents such as short circuits and fires, seriously threatening people's lives and property.
[0004] In addition, traditional cables generally have a significant problem during long-term use - blooming. Blooming refers to the gradual migration of additives (such as plasticizers, stabilizers, etc.) inside the cable to the surface, forming a layer of white or colored powdery substances. This phenomenon not only seriously affects the appearance of the cable, but also leads to the following problems:
[0005] Degradation of electrical performance: The frost layer will reduce the insulation performance of the cable, increase the risk of leakage, and affect the electrical safety of the cable.
[0006] Weakened mechanical properties: The formation of a frost layer will make the cable surface rough, reduce its wear resistance and tensile strength, and increase the risk of damage to the cable during installation and use.
[0007] Shortened service life: Frosting accelerates the aging process of the cable, shortens the service life of the cable, and increases maintenance and replacement costs. Summary of the invention
[0008] In view of the shortcomings of the prior art, the present invention provides a cable product and a manufacturing method for inhibiting frosting. The purpose of the present invention is to provide a new type of cable product and a preparation method thereof, so that the cable product not only has excellent flame retardant properties, but also can keep the surface clean during long-term use, avoid the occurrence of frosting, thereby improving the overall performance and service life of the cable.
[0009] A first aspect of the present invention is to provide a method for manufacturing a cable product that inhibits blooming, comprising the following steps:
[0010] Step S1: preparing an ammonium polyphosphate composite flame retardant modified by an aluminum hydroxide coating layer, i.e., a modified flame retardant;
[0011] Step S2: preparing a barrier fiber membrane-adsorbent composite material with adsorption function, namely, a modified barrier fiber membrane;
[0012] Step S3: combining the modified barrier fiber membrane with the cable base material containing the modified flame retardant to form a blank surface, thereby obtaining a cable product with anti-floating properties.
[0013] As a further optimization scheme for the manufacturing method of cable products that inhibit frosting, in step S1, ammonium polyphosphate and melamine polyphosphate are mixed in a mass ratio of 3-5:1, and refined and sieved to obtain composite micropowder; silicone powder and aluminum sulfate are ground in a mass ratio of 1:5-8, and deionized water is added, and the mass ratio of deionized water to powder is 30-50:1 to form a dispersed aluminum sulfate composite liquid; in an ammonia atmosphere, the aluminum sulfate composite liquid is sprayed on the surface of the composite micropowder and dried to form an aluminum hydroxide coating layer to obtain a modified flame retardant.
[0014] As a further optimization scheme for the manufacturing method of cable products that inhibit blooming, in step S1, ammonium polyphosphate and melamine polyphosphate are mixed in a mass ratio of (3-5):1, and sieved after micro-processing to obtain a composite micropowder with a particle size of less than 5 μm; silicone powder and aluminum sulfate are ground in a mass ratio of 1:(5-8), and deionized water is added, and the mass ratio of deionized water to powder is (30-50):1 to prepare a dispersed aluminum sulfate composite liquid; the composite micropowder is placed in a closed container, filled with ammonia and stirred at a high speed at 800-1200 rpm, and the temperature is controlled at 35-45°C; the aluminum sulfate composite liquid is sprayed into the container using a high-pressure spray gun to form an aluminum hydroxide coating layer; and after fluidized bed drying at 100-120°C, a modified flame retardant is obtained.
[0015] As a further optimization scheme for the manufacturing method of cable products that inhibit frosting, in step S2, polyvinyl pyrrolidone is mixed with water, activated carbon powder is added as an adsorbent, and after sufficient stirring, a uniform spinning solution is obtained by filtering; the spinning solution is electrospun to form a barrier fiber membrane blank, and the barrier fiber membrane is dried to obtain a barrier fiber membrane; a layer of activated carbon powder is attached to one side of the barrier fiber membrane to make a modified barrier fiber membrane with adsorption function.
[0016] As a further optimization scheme for the manufacturing method of cable products that inhibit frosting, in step S2, polyvinyl pyrrolidone and water are mixed in a mass ratio of (10-20):100, and adsorbent activated carbon powder is added, the mass ratio of activated carbon powder to water is (5-10):100, and the mixture is stirred evenly; the mixture is filtered using a filter membrane with a pore size of 0.2-0.45μm to obtain a homogeneous spinning solution; the spinning solution is spun under the conditions of an electrostatic voltage of 10-25kV, a spinneret diameter of 0.1-0.5mm, and a plate spacing of 20-30cm to form a barrier fiber membrane blank; the blank is then placed in a vacuum drying oven at 60-90°C to dry to obtain a barrier fiber membrane; a layer of activated carbon powder is evenly attached to a single side of the barrier fiber membrane to prepare a barrier fiber membrane-adsorbent composite material, i.e., a modified barrier fiber membrane.
[0017] As a further optimization scheme for the manufacturing method of cable products that inhibit frosting, in step S3, the modified flame retardant, filler, lubricating agent and silicone oil are preliminarily mixed; then chloroprene rubber, polyvinyl chloride and compatibilizer are added, and stirring is continued until uniformly mixed; the material is cooled and formed into a cable blank; the modified barrier fiber membrane is immersed in pre-vulcanized natural latex and cured to form a vulcanized rubber matrix film; the film is adhered to the outside of the cable blank, with the side without adsorbent in contact with the cable surface; it is cured by hot pressing, and finally a cable product that inhibits frosting is obtained.
[0018] As a further optimization scheme for the manufacturing method of the cable product with anti-blooming, in step S3, 40-50 parts by weight of the modified flame retardant, 5-10 parts by weight of the filler, 0.5-1 parts by weight of the lubricating aid and 0.1-0.3 parts by weight of the silicone oil are preliminarily mixed at 100-120°C; then, 200-300 parts by weight of chloroprene rubber and 100-200 parts by weight of polyvinyl chloride, as well as 5-10 parts by weight of the compatibilizer are added, and stirring is continued until the mixture is uniform; after the material is cooled, it is fed into a counter-rotating twin-screw extruder, and the mixture is heated at 100-120°C in zone 1. The temperature of each zone is set as 100-150℃, 200-160℃, 300-190℃, 400-170℃, and 500-180℃ for melt extrusion, and the die surface is air-cooled and pelletized to obtain a blank; the modified barrier fiber membrane is impregnated in pre-vulcanized natural rubber latex, and a vulcanized rubber matrix film is formed after curing, and the film is adhered to the outside of the cable blank so that the side without adsorbent is in direct contact with the cable surface, and it is cured by hot pressing at 100-130℃ and a pressure of 1-1.5MPa for 20-40 minutes to obtain a cable product with anti-floating.
[0019] As a further optimization scheme for the method for manufacturing cable products that inhibit blooming, in step S3, the filler is selected from one or more of talc powder and wollastonite powder.
[0020] As a further optimization scheme for the manufacturing method of cable products that inhibit blooming, in step S3, the lubricating agent is polyethylene wax; and the compatibilizer is maleic anhydride grafted polypropylene.
[0021] The second aspect of the present invention is to provide a cable product that inhibits frost spraying, which is prepared by the above method.
[0022] Beneficial Effects
[0023] The invention not only improves the dispersibility and stability of the flame retardant itself, but also enhances its flame retardant performance through the preparation of the modified ammonium polyphosphate composite flame retardant. The use of the modified flame retardant enables the cable to quickly play a flame retardant role when encountering a fire, effectively slows down the spread of the flame, and improves the safety performance of the cable.
[0024] The present invention prepares a modified barrier fiber membrane-adsorbent composite material, which not only increases the mechanical strength of the cable at the physical level, making it more resistant to external damage, but also forms an effective barrier chemically to prevent harmful substances from corroding the internal structure of the cable, thereby ensuring the performance stability and reliability of the cable in long-term use.
[0025] The present invention successfully solves the problem of frost spraying that may occur during long-term use of cables by using a modified flame retardant and barrier fiber membrane-adsorbent composite material prepared by a specific process. The experimental results show that no frost spraying occurs in all samples during the one-year observation period, proving that the technical solution can effectively prevent the internal additives of the cable from migrating outward and keep the cable surface clean and smooth.
[0026] The cable products prepared by the present invention are suitable for multiple fields, especially for scenes with extremely high requirements for safety and reliability, such as high-rise buildings, underground facilities, nuclear power plants, etc. In addition, with the development of emerging industries such as new energy vehicles and smart grids, the cable products can also meet the growing demand for high-performance cables in these industries, showing broad application prospects. DETAILED DESCRIPTION
[0027] The present invention is further illustrated by specific examples below. These examples are exemplary and are intended to illustrate the problem and explain the present invention, but are not intended to be limiting.
[0028] 1. Preparation of modified flame retardant
[0029] First, ammonium polyphosphate (APP) and melamine polyphosphate (MPP) are mixed in a mass ratio of (3-5):1, and sieved after micro-processing to obtain a composite micropowder with a particle size of less than 5μm. Next, aluminum hydroxide coating is performed: silicone powder and aluminum sulfate are ground in a mass ratio of 1:(5-8), deionized water is added, and the mass ratio of deionized water to powder is (30-50):1 to prepare a dispersed aluminum sulfate composite liquid. The composite micropowder is placed in a closed container, filled with ammonia and stirred at high speed at 800-1200rpm, and the temperature is controlled at 35-45°C. Subsequently, the aluminum sulfate composite liquid is sprayed into the container using a high-pressure spray gun to form an aluminum hydroxide coating layer. Finally, after a fluidized bed drying treatment at 100-120°C, the modified ammonium polyphosphate composite flame retardant is obtained.
[0030] 2. Preparation of modified barrier fiber membrane
[0031] First, a spinning solution is prepared by mixing polyvinyl pyrrolidone with water in a mass ratio of (10-20):100, and adding adsorbent activated carbon powder, the mass ratio of activated carbon powder to water is (5-10):100, and then stirring the mixture to ensure uniform mixing. After stirring, the mixture is filtered using a filter membrane with a pore size of 0.2-0.45μm to obtain a homogeneous spinning solution. Subsequently, the prepared spinning solution is spun under the conditions of an electrostatic voltage of 10-25kV, a spinneret diameter of 0.1-0.5mm, and a plate spacing of 20-30cm to form a barrier fiber membrane blank. The blank is then placed in a vacuum drying oven at 60-90°C for 24 hours to remove the residual solvent and obtain a barrier fiber membrane. Finally, a barrier fiber membrane-adsorbent composite material is prepared by uniformly attaching a layer of activated carbon powder to a single side of the barrier fiber membrane.
[0032] 3. Preparation of cable products
[0033] 40-50 parts by weight of the composite modified ammonium polyphosphate flame retardant, 5-10 parts by weight of filler, 0.5-1 parts by weight of lubricating aid and 0.1-0.3 parts by weight of silicone oil are put into a high-speed mixer and stirred at high speed for 15-20 minutes at 100-120°C to achieve preliminary mixing. Subsequently, 200-300 parts by weight of chloroprene rubber and 100-200 parts by weight of polyvinyl chloride as a base material and 5-10 parts by weight of a compatibilizer are added, and stirring is continued for 3-5 minutes until the mixture is completely mixed, and then the materials are transferred to a cold mixer for cooling. Next, the cooled material is fed into an extruder equipped with a counter-rotating twin screw with a diameter of 45 mm and an aspect ratio of 20:1, and melt extruded according to the set temperature of each zone (100-120°C for zone 1, 150-160°C for zone 2, 180-190°C for zone 3, 160-170°C for zone 4, and 130-140°C for zone 5), and pelletized by air-cooled die face. At the same time, the barrier fiber membrane-adsorbent composite material is first impregnated in pre-vulcanized natural rubber latex, and after curing, a stable vulcanized rubber matrix is formed to obtain a film with anti-blooming function. Finally, the anti-blooming film is tightly attached to the outside of the cable, ensuring that the side without adsorbent is in direct contact with the cable surface, and is firmly fixed to the cable by hot pressing at 100-130°C and a pressure of 1-1.5MPa for 20-40 minutes, so as to obtain a cable product that inhibits blooming.
[0034] The filler is selected from one or more of talc powder and wollastonite powder; the lubricating agent is polyethylene wax; and the compatibilizer is maleic anhydride grafted polypropylene.
[0035] The above scheme achieves effective protection for cable products by combining the dual protection mechanisms of flame retardant surface modification and barrier fiber membrane. On the one hand, by forming an aluminum hydroxide coating on the surface of the flame retardant, it not only improves the dispersibility and stability of the flame retardant, but also effectively prevents the flame retardant and other compounding agents from migrating from the inside of the cable to the surface, avoiding the occurrence of frosting. On the other hand, the application of barrier fiber membrane-adsorbent composite material further enhances the protection ability of the cable surface, forming a physical and chemical dual barrier to ensure that the cable surface remains clean and smooth during long-term use.
[0036] The modified flame retardant has an aluminum hydroxide coating, which not only enhances the flame retardant properties, but also greatly improves the heat resistance and water resistance of the material. Therefore, even in harsh environments such as high temperature and high humidity, the cable can maintain good performance, extend the service life of the product, and reduce maintenance costs.
[0037] The barrier fiber membrane introduced not only provides additional protection in terms of chemical properties, but also enhances the mechanical strength of the cable at the physical level. The combination of polyvinyl pyrrolidone and activated carbon powder makes the barrier fiber membrane both soft and tough, which can effectively resist damage caused by external forces, while maintaining the flexibility of the cable for easy installation and use.
[0038] Based on the above characteristics, the prepared cable products will be widely suitable for use in multiple fields such as power transmission, communication, and construction, especially in situations where safety and reliability are required to be high. For example, in environments such as high-rise buildings, underground facilities, and nuclear power plants, cables not only need to have excellent electrical properties, but also need to have excellent flame retardancy and anti-frost capabilities to ensure the long-term stable operation of the system. For another example, with the development of industries such as new energy vehicles and smart grids, the demand for high-performance cables is increasing, and the cable products provided by the present invention can meet the high standards for product performance and safety in these emerging markets.
[0039] Example 1
[0040] 1. Preparation of modified flame retardant
[0041] First, ammonium polyphosphate (APP) and melamine polyphosphate (MPP) are mixed in a mass ratio of 3:1, and sieved after micro-processing to obtain a composite micropowder with a particle size of less than 5μm. Next, aluminum hydroxide coating is performed: silicone powder and aluminum sulfate are ground in a mass ratio of 1:5, deionized water is added, and the mass ratio of deionized water to powder is 30:1 to prepare a dispersed aluminum sulfate composite liquid. The composite micropowder is placed in a closed container, filled with ammonia and stirred at a high speed at 900rpm, and the temperature is controlled at 40°C. Subsequently, the aluminum sulfate composite liquid is sprayed into the container using a high-pressure spray gun to form an aluminum hydroxide coating layer. Finally, after 110°C fluidized bed drying treatment, the modified ammonium polyphosphate composite flame retardant is obtained.
[0042] 2. Preparation of modified barrier fiber membrane
[0043] First, the spinning solution was prepared by mixing polyvinyl pyrrolidone with water in a mass ratio of 10:100, and adding adsorbent activated carbon powder, the mass ratio of activated carbon powder to water was 5:100, and then the mixture was stirred to ensure uniform mixing. After stirring, the mixture was filtered using a filter membrane with a pore size of 0.3μm to obtain a homogeneous spinning solution. Subsequently, the prepared spinning solution was spun under the conditions of an electrostatic voltage of 15kV, a spinneret diameter of 0.3mm, and a plate spacing of 25cm to form a barrier fiber membrane blank. The blank was then placed in a vacuum drying oven at 70°C for 24 hours to remove the residual solvent, and finally a barrier fiber membrane with a thickness of about 2.0μm was obtained. Finally, a barrier fiber membrane-adsorbent composite material was prepared by uniformly attaching a layer of activated carbon powder to a single side of the barrier fiber membrane.
[0044] 3. Preparation of cable products
[0045] 40 parts by weight of composite modified ammonium polyphosphate flame retardant, 5 parts by weight of filler, 0.8 parts by weight of lubricating aid and 0.2 parts by weight of silicone oil were put into a high-speed mixer and stirred at high speed for 20 minutes at 110°C to achieve preliminary mixing. Subsequently, 200 parts by weight of chloroprene rubber and 100 parts by weight of polyvinyl chloride were added as substrates, as well as 8 parts by weight of compatibilizer, and stirring was continued for 5 minutes until completely mixed, after which the material was transferred to a cold mixer for cooling. Next, the cooled material was fed into an extruder equipped with a counter-rotating twin-screw with a diameter of 45 mm and an aspect ratio of 20:1, and melt extruded according to the set temperature of each zone (100-120°C in zone 1, 150-160°C in zone 2, 180-190°C in zone 3, 160-170°C in zone 4, and 130-140°C in zone 5), and air-cooled die face pelletizing was used for molding. At the same time, the barrier fiber film-adsorbent composite material is first impregnated in pre-vulcanized natural rubber latex, and then solidified to form a stable vulcanized rubber matrix, thereby obtaining a film with anti-blooming function. Finally, the anti-blooming film is tightly attached to the outside of the cable, ensuring that the side without adsorbent is in direct contact with the cable surface, and is firmly fixed to the cable by hot pressing at 120°C and 1.5MPa for 30 minutes, thus obtaining a cable product that inhibits blooming.
[0046] In this embodiment, the filler is talcum powder; the lubricating agent is polyethylene wax; and the compatibilizer is maleic anhydride grafted polypropylene.
[0047] Example 2
[0048] 1. Preparation of modified flame retardant
[0049] First, ammonium polyphosphate (APP) and melamine polyphosphate (MPP) are mixed in a mass ratio of 5:1, and sieved after micro-processing to obtain a composite micropowder with a particle size of less than 5μm. Next, aluminum hydroxide coating is performed: silicone powder and aluminum sulfate are ground in a mass ratio of 1:8, deionized water is added, and the mass ratio of deionized water to powder is 50:1 to prepare a dispersed aluminum sulfate composite liquid. The composite micropowder is placed in a closed container, filled with ammonia and stirred at a high speed at 900rpm, and the temperature is controlled at 40°C. Subsequently, the aluminum sulfate composite liquid is sprayed into the container using a high-pressure spray gun to form an aluminum hydroxide coating layer. Finally, after 110°C fluidized bed drying treatment, the modified ammonium polyphosphate composite flame retardant is obtained.
[0050] 2. Preparation of modified barrier fiber membrane
[0051] First, the spinning solution was prepared by mixing polyvinyl pyrrolidone with water in a mass ratio of 20:100, and adding adsorbent activated carbon powder, the mass ratio of activated carbon powder to water was 10:100, and then the mixture was stirred to ensure uniform mixing. After stirring, the mixture was filtered using a filter membrane with a pore size of 0.3μm to obtain a homogeneous spinning solution. Subsequently, the prepared spinning solution was spun under the conditions of an electrostatic voltage of 15kV, a spinneret diameter of 0.3mm, and a plate spacing of 25cm to form a barrier fiber membrane blank. The blank was then placed in a vacuum drying oven at 70°C for 24 hours to remove the residual solvent, and finally a barrier fiber membrane with a thickness of about 2.0μm was obtained. Finally, a barrier fiber membrane-adsorbent composite material was prepared by uniformly attaching a layer of activated carbon powder to a single side of the barrier fiber membrane.
[0052] 3. Preparation of cable products
[0053] 50 parts by weight of composite modified ammonium polyphosphate flame retardant, 10 parts by weight of filler, 0.8 parts by weight of lubricating aid and 0.2 parts by weight of silicone oil were put into a high-speed mixer and stirred at high speed for 20 minutes at 110°C to achieve preliminary mixing. Subsequently, 300 parts by weight of chloroprene rubber and 200 parts by weight of polyvinyl chloride were added as substrates, as well as 8 parts by weight of compatibilizer, and stirring was continued for 5 minutes until completely mixed, after which the material was transferred to a cold mixer for cooling. Next, the cooled material was fed into an extruder equipped with a counter-rotating twin-screw with a diameter of 45 mm and an aspect ratio of 20:1, and melt extruded according to the set temperature of each zone (100-120°C in zone 1, 150-160°C in zone 2, 180-190°C in zone 3, 160-170°C in zone 4, and 130-140°C in zone 5), and air-cooled die face pelletizing was used for molding. At the same time, the barrier fiber film-adsorbent composite material is first impregnated in pre-vulcanized natural rubber latex, and then solidified to form a stable vulcanized rubber matrix, thereby obtaining a film with anti-blooming function. Finally, the anti-blooming film is tightly attached to the outside of the cable, ensuring that the side without adsorbent is in direct contact with the cable surface, and is firmly fixed to the cable by hot pressing at 120°C and 1.5MPa for 30 minutes, thus obtaining a cable product that inhibits blooming.
[0054] In this embodiment, the filler is talcum powder; the lubricating agent is polyethylene wax; and the compatibilizer is maleic anhydride grafted polypropylene.
[0055] Example 3
[0056] 1. Preparation of modified flame retardant
[0057] First, ammonium polyphosphate (APP) and melamine polyphosphate (MPP) are mixed in a mass ratio of 4:1, and sieved after micro-processing to obtain a composite micropowder with a particle size of less than 5μm. Next, aluminum hydroxide coating is performed: silicone powder and aluminum sulfate are ground in a mass ratio of 1:6, deionized water is added, and the mass ratio of deionized water to powder is 40:1 to prepare a dispersed aluminum sulfate composite liquid. The composite micropowder is placed in a closed container, filled with ammonia and stirred at a high speed at 900rpm, and the temperature is controlled at 40°C. Subsequently, the aluminum sulfate composite liquid is sprayed into the container using a high-pressure spray gun to form an aluminum hydroxide coating layer. Finally, after 110°C fluidized bed drying treatment, the modified ammonium polyphosphate composite flame retardant is obtained.
[0058] 2. Preparation of modified barrier fiber membrane
[0059] First, the spinning solution was prepared by mixing polyvinyl pyrrolidone with water in a mass ratio of 15:100, and adding adsorbent activated carbon powder, the mass ratio of activated carbon powder to water was 8:100, and then the mixture was stirred to ensure uniform mixing. After stirring, the mixture was filtered using a filter membrane with a pore size of 0.3μm to obtain a homogeneous spinning solution. Subsequently, the prepared spinning solution was spun under the conditions of an electrostatic voltage of 15kV, a spinneret diameter of 0.3mm, and a plate spacing of 25cm to form a barrier fiber membrane blank. The blank was then placed in a vacuum drying oven at 70°C for 24 hours to remove the residual solvent, and finally a barrier fiber membrane with a thickness of about 2.0μm was obtained. Finally, a barrier fiber membrane-adsorbent composite material was prepared by uniformly attaching a layer of activated carbon powder to a single side of the barrier fiber membrane.
[0060] 3. Preparation of cable products
[0061] 45 parts by weight of composite modified ammonium polyphosphate flame retardant, 8 parts by weight of filler, 0.8 parts by weight of lubricating aid and 0.2 parts by weight of silicone oil were put into a high-speed mixer and stirred at high speed for 20 minutes at 110°C to achieve preliminary mixing. Subsequently, 250 parts by weight of chloroprene rubber and 150 parts by weight of polyvinyl chloride were added as substrates, as well as 8 parts by weight of compatibilizer, and stirring was continued for 5 minutes until completely mixed, after which the material was transferred to a cold mixer for cooling. Next, the cooled material was fed into an extruder equipped with a counter-rotating twin-screw with a diameter of 45 mm and an aspect ratio of 20:1, and melt extruded according to the set temperature of each zone (100-120°C in zone 1, 150-160°C in zone 2, 180-190°C in zone 3, 160-170°C in zone 4, and 130-140°C in zone 5), and air-cooled die face pelletizing was used for molding. At the same time, the barrier fiber film-adsorbent composite material is first impregnated in pre-vulcanized natural rubber latex, and then solidified to form a stable vulcanized rubber matrix, thereby obtaining a film with anti-blooming function. Finally, the anti-blooming film is tightly attached to the outside of the cable, ensuring that the side without adsorbent is in direct contact with the cable surface, and is firmly fixed to the cable by hot pressing at 120°C and 1.5MPa for 30 minutes, thus obtaining a cable product that inhibits blooming.
[0062] In this embodiment, the filler is talcum powder; the lubricating agent is polyethylene wax; and the compatibilizer is maleic anhydride grafted polypropylene.
[0063] Example 4
[0064] 1. Preparation of modified flame retardant
[0065] First, ammonium polyphosphate (APP) and melamine polyphosphate (MPP) are mixed in a mass ratio of 4:1, and sieved after micro-processing to obtain a composite micropowder with a particle size of less than 5μm. Next, aluminum hydroxide coating is performed: silicone powder and aluminum sulfate are ground in a mass ratio of 1:6, deionized water is added, and the mass ratio of deionized water to powder is 40:1 to prepare a dispersed aluminum sulfate composite liquid. The composite micropowder is placed in a closed container, filled with ammonia and stirred at a high speed at 900rpm, and the temperature is controlled at 40°C. Subsequently, the aluminum sulfate composite liquid is sprayed into the container using a high-pressure spray gun to form an aluminum hydroxide coating layer. Finally, after 110°C fluidized bed drying treatment, the modified ammonium polyphosphate composite flame retardant is obtained.
[0066] 2. Preparation of modified barrier fiber membrane
[0067] First, the spinning solution was prepared by mixing polyvinyl pyrrolidone with water in a mass ratio of 15:100, and adding adsorbent activated carbon powder, the mass ratio of activated carbon powder to water was 8:100, and then the mixture was stirred to ensure uniform mixing. After stirring, the mixture was filtered using a filter membrane with a pore size of 0.3μm to obtain a homogeneous spinning solution. Subsequently, the prepared spinning solution was spun under the conditions of an electrostatic voltage of 15kV, a spinneret diameter of 0.3mm, and a plate spacing of 25cm to form a barrier fiber membrane blank. The blank was then placed in a vacuum drying oven at 70°C for 24 hours to remove the residual solvent, and finally a barrier fiber membrane with a thickness of about 2.0μm was obtained. Finally, a barrier fiber membrane-adsorbent composite material was prepared by uniformly attaching a layer of activated carbon powder to a single side of the barrier fiber membrane.
[0068] 3. Preparation of cable products
[0069] 45 parts by weight of composite modified ammonium polyphosphate flame retardant, 8 parts by weight of filler, 0.8 parts by weight of lubricating aid and 0.2 parts by weight of silicone oil were put into a high-speed mixer and stirred at high speed for 20 minutes at 110°C to achieve preliminary mixing. Subsequently, 280 parts by weight of chloroprene rubber and 160 parts by weight of polyvinyl chloride were added as substrates, as well as 8 parts by weight of compatibilizer, and stirring was continued for 5 minutes until completely mixed, after which the material was transferred to a cold mixer for cooling. Next, the cooled material was fed into an extruder equipped with a counter-rotating twin-screw with a diameter of 45 mm and an aspect ratio of 20:1, and melt extruded according to the set temperature of each zone (100-120°C in zone 1, 150-160°C in zone 2, 180-190°C in zone 3, 160-170°C in zone 4, and 130-140°C in zone 5), and air-cooled die face pelletizing was used for molding. At the same time, the barrier fiber film-adsorbent composite material is first impregnated in pre-vulcanized natural rubber latex, and then solidified to form a stable vulcanized rubber matrix, thereby obtaining a film with anti-blooming function. Finally, the anti-blooming film is tightly attached to the outside of the cable, ensuring that the side without adsorbent is in direct contact with the cable surface, and is firmly fixed to the cable by hot pressing at 120°C and 1.5MPa for 30 minutes, thus obtaining a cable product that inhibits blooming.
[0070] In this embodiment, the filler is wollastonite powder; the lubricating agent is polyethylene wax; and the compatibilizer is maleic anhydride grafted polypropylene.
[0071] Example 5
[0072] 1. Preparation of modified flame retardant
[0073] First, ammonium polyphosphate (APP) and melamine polyphosphate (MPP) are mixed in a mass ratio of 4:1, and sieved after micro-processing to obtain a composite micropowder with a particle size of less than 5μm. Next, aluminum hydroxide coating is performed: silicone powder and aluminum sulfate are ground in a mass ratio of 1:5, deionized water is added, and the mass ratio of deionized water to powder is 50:1 to prepare a dispersed aluminum sulfate composite liquid. The composite micropowder is placed in a closed container, filled with ammonia and stirred at a high speed at 900rpm, and the temperature is controlled at 40°C. Subsequently, the aluminum sulfate composite liquid is sprayed into the container using a high-pressure spray gun to form an aluminum hydroxide coating layer. Finally, after 110°C fluidized bed drying treatment, the modified ammonium polyphosphate composite flame retardant is obtained.
[0074] 2. Preparation of modified barrier fiber membrane
[0075] First, the spinning solution was prepared by mixing polyvinyl pyrrolidone with water in a mass ratio of 20:100, and adding adsorbent activated carbon powder, the mass ratio of activated carbon powder to water was 6:100, and then the mixture was stirred to ensure uniform mixing. After stirring, the mixture was filtered using a filter membrane with a pore size of 0.3μm to obtain a homogeneous spinning solution. Subsequently, the prepared spinning solution was spun under the conditions of an electrostatic voltage of 15kV, a spinneret diameter of 0.3mm, and a plate spacing of 25cm to form a barrier fiber membrane blank. The blank was then placed in a vacuum drying oven at 70°C for 24 hours to remove the residual solvent, and finally a barrier fiber membrane with a thickness of about 2.0μm was obtained. Finally, a barrier fiber membrane-adsorbent composite material was prepared by uniformly attaching a layer of activated carbon powder to a single side of the barrier fiber membrane.
[0076] 3. Preparation of cable products
[0077] 50 parts by weight of composite modified ammonium polyphosphate flame retardant, 7 parts by weight of filler, 0.8 parts by weight of lubricating aid and 0.2 parts by weight of silicone oil were put into a high-speed mixer and stirred at high speed for 20 minutes at 110°C to achieve preliminary mixing. Subsequently, 300 parts by weight of chloroprene rubber and 100 parts by weight of polyvinyl chloride were added as substrates, as well as 8 parts by weight of compatibilizer, and stirring was continued for 5 minutes until completely mixed, after which the material was transferred to a cold mixer for cooling. Next, the cooled material was fed into an extruder equipped with a counter-rotating twin-screw with a diameter of 45 mm and an aspect ratio of 20:1, and melt extruded according to the set temperature of each zone (100-120°C in zone 1, 150-160°C in zone 2, 180-190°C in zone 3, 160-170°C in zone 4, and 130-140°C in zone 5), and air-cooled die face pelletizing was used for molding. At the same time, the barrier fiber film-adsorbent composite material is first impregnated in pre-vulcanized natural rubber latex, and then solidified to form a stable vulcanized rubber matrix, thereby obtaining a film with anti-blooming function. Finally, the anti-blooming film is tightly attached to the outside of the cable, ensuring that the side without adsorbent is in direct contact with the cable surface, and is firmly fixed to the cable by hot pressing at 120°C and 1.5MPa for 30 minutes, thus obtaining a cable product that inhibits blooming.
[0078] In this embodiment, the filler is wollastonite powder; the lubricating agent is polyethylene wax; and the compatibilizer is maleic anhydride grafted polypropylene.
[0079] Test example
[0080] In order to verify the anti-frost effect of the prepared cable products, a long-term observation experiment of 365 days was carried out on the samples in Examples 1 to 5. Five parallel samples were prepared for each sample to reduce the influence of accidental factors on the experimental results. During the experiment, all samples were placed in a standard laboratory environment, and the environmental conditions met the temperature (23±5℃) and humidity (50±10%RH). The surface state of the samples was checked regularly every 15 days, and any possible frosting phenomenon was recorded, including but not limited to the appearance of white or colored powdery substances. The results are shown in Table 1.
[0081] Table 1
[0082]
[0083] As shown in Table 1, the surface conditions of the samples of all the examples at 90 days, 180 days and 365 days were all "no frosting". During the 365-day observation period, no frosting was found on the surface of all the samples, indicating that the barrier fiber membrane-adsorbent composite material used can effectively prevent the additives inside the cable from migrating to the surface, thereby avoiding the occurrence of frosting. This result verifies the stability and reliability of the cable products prepared in the examples in long-term use.
[0084] The above embodiments are exemplary, and their purpose is to illustrate the technical concept and features of the present invention so that people familiar with the technology in this field can understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for manufacturing a cable product that inhibits blooming, characterized in that: The following steps are involved: Step S1: preparing an ammonium polyphosphate composite flame retardant modified by an aluminum hydroxide coating layer, i.e., a modified flame retardant; Step S2: preparing a barrier fiber membrane-adsorbent composite material with adsorption function, namely, a modified barrier fiber membrane; Step S3: combining the modified barrier fiber membrane with the cable base material containing the modified flame retardant to form a blank surface, thereby obtaining a cable product with anti-floating properties.
2. The method for manufacturing a cable product with anti-frost according to claim 1, characterized in that: In step S1, ammonium polyphosphate and melamine polyphosphate are mixed in a mass ratio of 3-5:1, and refined and sieved to obtain composite micropowder; silicone powder and aluminum sulfate are ground in a mass ratio of 1:5-8, and deionized water is added, and the mass ratio of deionized water to powder is 30-50:1 to form a dispersed aluminum sulfate composite liquid; in an ammonia atmosphere, the aluminum sulfate composite liquid is sprayed on the surface of the composite micropowder and dried to form an aluminum hydroxide coating layer to obtain a modified flame retardant.
3. The method for manufacturing a cable product with anti-blooming properties according to claim 1, characterized in that: In step S1, ammonium polyphosphate and melamine polyphosphate are mixed in a mass ratio of (3-5):1, and sieved after being processed by a micro-machine to obtain a composite micropowder with a particle size of less than 5 μm; silicone powder and aluminum sulfate are ground in a mass ratio of 1:(5-8), and deionized water is added, and the mass ratio of deionized water to powder is (30-50):1 to prepare a dispersed aluminum sulfate composite liquid; the composite micropowder is placed in a closed container, filled with ammonia and stirred at a high speed at 800-1200 rpm, and the temperature is controlled at 35-45°C; the aluminum sulfate composite liquid is sprayed into the container using a high-pressure spray gun to form an aluminum hydroxide coating layer; and after being subjected to fluidized bed drying treatment at 100-120°C, a modified flame retardant is obtained.
4. The method for manufacturing a cable product with anti-frost according to claim 1, characterized in that: In step S2, polyvinyl pyrrolidone is mixed with water, activated carbon powder is added as an adsorbent, and after sufficient stirring, a uniform spinning solution is obtained by filtering; the spinning solution is electrospun to form a barrier fiber membrane blank, and the barrier fiber membrane is dried to obtain a barrier fiber membrane; a layer of activated carbon powder is attached to one side of the barrier fiber membrane to prepare a modified barrier fiber membrane with adsorption function.
5. The method for manufacturing a cable product with anti-blooming properties according to claim 1, characterized in that: In step S2, polyvinyl pyrrolidone and water are mixed in a mass ratio of (10-20):100, and activated carbon powder as an adsorbent is added, the mass ratio of activated carbon powder to water is (5-10):100, and the mixture is stirred evenly; the mixture is filtered using a filter membrane with a pore size of 0.2-0.45 μm to obtain a homogeneous spinning solution; the spinning solution is spun under the conditions of an electrostatic voltage of 10-25 kV, a spinneret diameter of 0.1-0.5 mm, and a plate spacing of 20-30 cm to form a barrier fiber membrane blank; the blank is then placed in a vacuum drying oven at 60-90°C to dry to obtain a barrier fiber membrane; a layer of activated carbon powder is evenly attached to a single side of the barrier fiber membrane to prepare a barrier fiber membrane-adsorbent composite material, i.e., a modified barrier fiber membrane.
6. The method for manufacturing a cable product with anti-frost according to claim 1, characterized in that: In step S3, the modified flame retardant, filler, lubricating agent and silicone oil are preliminarily mixed; then chloroprene rubber, polyvinyl chloride and compatibilizer are added, and stirring is continued until uniformly mixed; After the material is cooled, it is formed into a cable blank; the modified barrier fiber membrane is impregnated in pre-vulcanized natural latex and cured to form a vulcanized rubber matrix film; the film is adhered to the outside of the cable blank, with the side without adsorbent in contact with the cable surface; it is cured by hot pressing, and finally a cable product with anti-floating properties is obtained.
7. The method for manufacturing a cable product with anti-frost according to claim 1, characterized in that: In step S3, 40-50 parts by weight of a modified flame retardant, 5-10 parts by weight of a filler, 0.5-1 parts by weight of a lubricating aid and 0.1-0.3 parts by weight of silicone oil are preliminarily mixed at 100-120° C.; then, 200-300 parts by weight of chloroprene rubber and 100-200 parts by weight of polyvinyl chloride, as well as 5-10 parts by weight of a compatibilizer are added, and stirring is continued until the mixture is uniform; after the material is cooled, it is fed into a counter-rotating twin-screw extruder, and the temperature of zone 1 is 100-120° C., zone 2 is 150-160° C., and zone 3 is 150-160° C. The temperatures of zone 3, zone 4, and zone 5 are set at 180-190°C, 160-170°C, and 130-140°C, respectively, for melt extrusion, and the blank is formed by air-cooling the die surface and pelletizing; the modified barrier fiber membrane is impregnated in pre-vulcanized natural rubber latex, and a vulcanized rubber matrix film is formed after curing, and the film is adhered to the outside of the cable blank so that the side without adsorbent is in direct contact with the cable surface, and is cured by hot pressing at 100-130°C and a pressure of 1-1.5MPa for 20-40 minutes to obtain a cable product with anti-floating properties.
8. The method for manufacturing a cable product with anti-blooming properties according to claim 6 or 7, characterized in that: In step S3, the filler is selected from one or more of talc powder and wollastonite powder.
9. The method for manufacturing a cable product with anti-blooming properties according to claim 6 or 7, characterized in that: In step S3, the lubricating agent is polyethylene wax; and the compatibilizer is maleic anhydride grafted polypropylene.
10. A cable product for inhibiting frost spraying, characterized in that: The method is prepared by any one of claims 1 to 9.